Exploring Gaps in Halal Audit Procedures for Meat Products in Brunei Darussalam: A Qualitative Literature Review - Hanni, Siti Nazerah A.; Hashim, Norkhairiah (Arbain Publishing, 2025)
Halal food is not only a religious requirement for Muslims but also encompasses the principles of purity, wholesomeness, and quality, as emphasised in the Holy Qur’an (2:168). The growing global demand for halal meat underscores the importance of ensuring both halal compliance and food safety. This study examines halal audit procedures in Brunei Darussalam, focusing on their role in assuring the safety and quality of local and imported halal meat products. Employing a qualitative approach through document analysis and literature review, the research identifies significant gaps in current halal audit frameworks, including the absence of clearly defined Halal Critical Control Points (HCCPs) and insufficient integration of food safety and quality assurance within audit practices. Challenges such as cross-contamination risks and inadequate segregation in the halal meat supply chain further complicate assurance efforts. The findings highlight that existing audit tend to emphasise religious compliance while adopting a passive approach to food safety, potentially undermining consumer trust. Recommendations include developing standardized audit frameworks incorporating CCPs, enhancing auditor training, and strengthening monitoring and enforcement mechanisms. This study provides a foundation for future empirical research and contributes to improving halal assurance systems to meet both religious and consumer expectations for safe, high-quality halal meat.